From Dual to Unified Employment Protection: Transition and Steady State - Juan J. Dolado; Etienne Lalé; Nawid Siassi (Institute for the Study of Labor (IZA), 2016)
This paper analyses the optimal design of a single open-ended contract (SOEC) and studies the political economy of moving towards such a SOEC in a labour market where employment protection is highly discontinuous. We develop a computationally tractable approach to compare two economic environments: one with a large employment protection gap after a short tenure, and another one with a SOEC featuring a smooth tenure profile. For illustrative purposes, we specialise the discussion of such choices to Spain, a country often considered as an epitome of a labour market with dual employment protection. We show that a SOEC has the potential of bringing substantial improvements in equilibrium allocations and welfare. We provide estimates for the eligibility rule and tenure profile of the optimal SOEC, defined as the contract maximising the steady-state lifetime utility of new labour-market entrants. Finally, we use the model to identify winners and losers among younger and older workers in the transitional path of such a reform, and evaluate its political support.
Keywords: H29; J33; J65; 330; single contract; employment protection; dualism; labour market reform